Are Vocational High School Students Ready to be Entrepreneur? - Soputan, Grace J. (INVOTEC, 2017)
The challenges of vocational education is to answer the changed faced by people nowadays as well as to prepare the labor in particular number and quality according to the needs of different sectors, especially industrial and service sector. To prepare the graduate of vocational high school who fulfills the qualification of labor market, then the competency of the graduates of vocational high school need to be regenerated and increased. This research is to analyze the influence of entrepreneurships education and work training to students’ entrepreneur attitude. Students’ entrepreneur attitude can be seen from self-confidence aspect, oriented on task and result, risk takers, leaderships, originality and future oriented. Data was collected from 113 students at SMK N 2 Tondano by doing proportional sampling technique. The result of the research found that students’ entrepreneur attitude can be shaped through entrepreneurship education at school and work training or take apprentice programs outside of schools.